Separation mechanism of lattice-bound trace elements from quartz by KCl-doping calcination and pressure leaching. (15th August 2018) - Lin, Min; Pei, Zhenyu; Li, Yubiao; Liu, Yuanyuan; Wei, Zhenlun; Lei, Shaomin
Graphical abstract: Highlights: An efficient method to separate trace lattice elements from quartz is presented. Trace lattice elements are activated during phase transformation of quartz. Trace lattice impurities are removed from quartz by oxidation and chlorination. Abstract: Trace elements bound in quartz lattice are efficiently removed by KCl-doping calcination and pressure leaching. Removal rate of lattice Al reaches 73.5% when 70.4% of lattice-bound trace elements are removed from quartz sand at optimum conditions. The lattice-bound trace elements in quartz are activated by high-temperature calcination, released during phase transformation from α-quartz to cristobalite, diffused to quartz surface by surface enrichment, and removed by oxidation, chlorination and pressure leaching.